21st Century Learning Skills and Their Influence on Perceived Organizational Effectiveness among Registered Nurses' Perceptions in Private Hospitals, Northeastern Thailand: A Cross-Sectional Study. - Nonthamat, Amphawan; Juntachum, Wanchanok (Pacific Rim International Journal of Nursing Research)
Organizational effectiveness is a critical component in sustaining healthcare service quality, workforce performance, and the adaptability of healthcare organizations within rapidly changing health systems. The increasing complexity of healthcare delivery and the growing demand for registered nurses underscore the importance of 21st century learning skills, including critical thinking and problem-solving; collaboration and teamwork with leadership; communication and information literacy; cross-cultural competence; digital and information and communication technology literacy; creativity and innovation; self-directed career and lifelong learning as essential competencies for contemporary nursing practice. However, empirical evidence regarding how these comprehensive skills influence organizational effectiveness remains limited, particularly within the highly competitive context of private hospitals in Northeastern Thailand. To address this research gap, this cross-sectional descriptive study aimed to examine the influence of 21st century learning skills on perceived organizational effectiveness among registered nurses working in four private hospitals in Northeastern Thailand. Data were collected from a sample of 230 registered nurses using three structured questionnaires: a Personal Characteristics Questionnaire, the 21st Century Learning Skills Questionnaire, and the Perceived Organizational Effectiveness Questionnaire. Data were subjected to statistical analysis, including descriptive statistics, Pearson's correlation coeff icient, and stepwise multiple linear regression. The results revealed that the participants had both organizational effectiveness and overall 21st century learning skills at a high level. Pearson's correlation analysis demonstrated that all dimensions of 21st century learning skills were positively and signif icantly associated with perceived organizational effectiveness. Stepwise multiple regression analysis indicated that cross-cultural understanding skills, career and learning self-reliance skills, critical thinking and problem-solving skills, and collaboration, teamwork, and leadership skills were signif icant predictors of perceived organizational effectiveness, collectively explaining 76.5% of the variance. These f indings highlight the importance of developing 21st century learning skills among registered nurses to enhance organizational effectiveness and support the eff icient, sustainable operation of healthcare organizations.